Sexual Behaviour of Commercial Sex Workers; Islamic Perspectives and Health - Achyar Zein; Watni Marpaung (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
Prostitution or Commercial Sex Worker (CSW) is exchanging money for sexual services. Someone who sells sexual services is referred to as a prostitute, although the term commercial sex worker is now more commonly used. Method: This study is a qualitative look at how prostitutes in Medan and Batam feel about God. When looking for information for a study on how prostitutes' religion affects their work and lives, it was found that there is not much to go on. To obtain this information, interviews were conducted. In these informal interviews, the participants may be unaware they are being interviewed systematically. The data collection strategy included in-depth interviews and observation of directly involved prostitutes. This method was used to determine how prostitutes thought about religious patterns and to improve and develop the theory. Results: Most Commercial Sex Workers (CSWs) in Medan, Indonesia, are generally unfamiliar with the actual meaning of religion. You can use "Islam" even if you have never done the required worship. In addition, prostitution is viewed as a fact of life experienced alone. In general, the religious knowledge and comprehension of Commercial Sex Workers (CSWs) in Batam are limited.Conclusion: Even more interesting, they know that sin and punishment are different things that do not overlap. Thus, as do prostitution-related activities, prayer, and other forms of worship continue. The causes of prostitution can be broken down into two categories: economic factors and basic needs. In comparison, the following factor is the result of association and friendship. In addition to these two factors, there are at least lifestyle, and sexuality needs as derivative factors.